The Meaning of Smara Sādhanā in The Kama Tattwa Manuscripts: A Tantrāyāna Philosophy Perspective - Gede Agus Siswadi; Lasiyo Lasiyo; Rr. Siti Murtiningsih (Jayapangus Press, 2026)
Talking about sex is often regarded as a taboo subject and something that should not be discussed in public. In fact, understanding the true nature of sexuality is very important and even necessary in order to avoid deviant sexual behavior. This study aims to examine the philosophical dimension of Smara Sādhanā, or sacred sexuality, in the Kama Tattwa manuscript through the perspective of Tantrāyāna philosophy, by referring to three principal Balinese Hindu palm-leaf manuscripts, namely Smara Krida Laksana, Resi Sembina, and Rahasya Sanggama. This research employs a qualitative method with a hermeneutic approach. The findings show that Smara Sādhanā represents an integral spiritual system grounded in Tantrāyāna non-dualism, in which sexual union symbolically represents and simultaneously actualizes the metaphysical unity between Puruṣa (consciousness) and Prakṛti (creative energy). Ontologically, sexuality is understood as a manifestation of cosmic energy; epistemologically, knowledge of sexuality is derived from the authority of sacred texts (śabda pramāṇa), direct experience (pratyakṣa), reasoning (anumāna), and ultimately reaches direct spiritual realization (aparokṣānubhūti); and axiologically, the concept of Smara Sādhanā upholds values of bodily sanctity, respect, compassion, and spiritual responsibility. Thus, the human body is viewed as a microcosm, and sanggama (sexual union) becomes a medium for attaining higher consciousness (ānanda). This study finds that the Kama Tattwa manuscript contains a profound philosophical discourse on sacred sexuality that challenges reductionist and moralistic interpretations of sex. Instead, these texts present sexuality as a path of spiritual transformation integrated within dharma and ethical relations among human beings. The conclusion of this study is that, in the Hindu perspective, sex is regarded as a sacred activity and understood as a form of sādhanā, a view that is likewise emphasized in Tantrāyāna philosophy. Therefore, by understanding sexual activity as something sacred, it is expected that sexual conduct can be placed in accordance with the teachings of Dharma and that deviant sexual behavior can be avoided.